DINAMIKA PEMBAHARUAN HUKUM PERKAWINAN DI DUNIA ISLAM - Achmad Yazid Sinulingga; Faisar Ananda; Irwansyah, Irwansyah (Journal of Innovation Research and Knowledge, 2025)
The purpose of this essay is to investigate the mechanisms and approaches to Islamic marriage law reform in order to better understand this topic. Being normative juridical research, this study relies on secondary data sources such as statutory regulations as its main source, as well as tertiary sources like electronic media and dictionaries that explain both primary and secondary sources of law. This research's findings reveal that Islamic marriage law is undergoing a renewal process and that there are ways to modify it.